Molek Imagery and the Slaughter of Gog in Ezekiel 38 and 39 - Irwin, Brian Payl (Journal for the study of the Old Testament, 1995)
This study focuses on chs. 38 and 39 of the book of Ezekiel, arguing that the sacrificial imagery found in them is not 'generic' but reflects an understanding of the Molek cult. In this respect, Ezekiel 38 and 39 is comparable to Jeremiah 7 and Isaiah 30, the latter of which has recently been shown by John Day to invoke Molek cult imagery to describe the mass destruction of a foreign power.